Shrinkage Properties of Insulator Ceramic Body Porcelain Formed Using Local Material - Hussain, It. F.; Hadi, M. F.; Khaleel, R. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work was carried out to investigate the shrinkage properties of insulator ceramic body, and the effect of changing the ratio of concentration of electrolyte solution on these properties. The electrical insulator body was prepared by using Iraqi local materials. These are :- kaolin Duakhla, Arudhuma Sand glass, and potash feldspar with weight percentage (45%, 25%,and 30%) respectively. The processes of milling, classification, mixing, forming and firing, through the process of mixing electrolyte solution and mineralizer were added at different concentrations for electrolyte solution, (1%, 0.7%, 0.5%, 0.2%, and 0.1%). The electrolyte solution was prepared by mixing sodium carbonate and sodium silicate by (2:1) ratio, while the mineralize, Zinc Oxide, was added at fixed weight percentage. The measurements were undertaken on rectangular sample burnt at sintering temperatures of (1250, 1300,and 1350) oC. The result was obtained at (0.5%) electrolyte solution concentration has highest total shrinkage at (1300,1350) oC sintering temperature and also highest firing shrinkage .So that, it is the best concentration to get material property of insulating